Pemilihan Lokasi Strategis Bisnis Bidang Kuliner Menggunakan Metode the Extended Promethee II - Lestari, Sri Poedji; Sudarsono, Bernadus Gunawan (STIKOM Tunas Bangsa Pematangsiantar, 2021)
Business in the culinary field is one type of business that will not die and be eroded by the times because as long as humans still need food, culinary business is the right business choice with large profits, but in a business in the culinary field there are still very many the business died because of several factors that were previously ignored by many groups such as non-strategic location, business location to market a product that is not strategic can cause 40% of failures in the culinary business will lead to bankruptcy. This is very unfortunate if from the start it was not anticipated by taking into account what criteria were appropriate in selecting locations in selecting locations not only based on rumors that the area was good for building a business in the culinary field, especially for a culinary company in opening new branches. A business can use a decision support system in analyzing and calculating the level of accuracy in selecting the desired location with the help of the Promethee II (Exprom II) extended method approach which is able to assess the criteria in building a culinary business appropriately and effectively.